2020
DOI: 10.1111/acps.13238
|View full text |Cite
|
Sign up to set email alerts
|

Familial risk and heritability of depression by age at first diagnosis in Danish twins

Abstract: Objective Familial and genetic factors seem to contribute to the development of depression but whether this varies with age at diagnosis remains unclear. We examined the influence of familial factors on the risk of depression by age at first diagnosis. Methods We included 23 498 monozygotic and 39 540 same‐sex dizygotic twins from the population‐based Danish Twin Registry, followed from 1977 through 2011 in nationwide registers. We used time‐to‐event analyses accounting for censoring and competing risk of deat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 29 publications
1
9
0
Order By: Relevance
“…21 Siblings and twin studies have shown inconsistency in sex differences in heritability of MD. 15,20,28,34 These differing findings could be due to methodological is- sues, as our study population was sampled in an unselected population using registry data, while the US study recruited participants based on volunteering, which often causes lack of representativeness to the general population. The findings could also be affected by the measurement of MD varying from diagnoses by physicians registered in hospital records to assessments using, for example, the Beck Depression Inventory II, which may be subject to different levels of detection related to sex.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…21 Siblings and twin studies have shown inconsistency in sex differences in heritability of MD. 15,20,28,34 These differing findings could be due to methodological is- sues, as our study population was sampled in an unselected population using registry data, while the US study recruited participants based on volunteering, which often causes lack of representativeness to the general population. The findings could also be affected by the measurement of MD varying from diagnoses by physicians registered in hospital records to assessments using, for example, the Beck Depression Inventory II, which may be subject to different levels of detection related to sex.…”
Section: Discussionmentioning
confidence: 98%
“…Additionally, the timing of MD in family members may be important as childhood and adolescence may be sensitive periods with shared environment with parents and siblings. Finally, women are twice as likely as men to experience MD, but these findings are inconsistent as some studies report no difference in MD risk between the sexes …”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…The twin population was relatively old at first diagnosis possible because they might have been treated earlier in general practice, but in a previous study on the same twin sample (Wium-Andersen et al, 2020) we evaluated the representativeness of our measure of incident depression in a supplementary analysis, including a population-based 5% sample of the non-twin Danish population. We also compared our estimates with a comprehensive study of the lifetime risk of mental disorders in Denmark (Momen et al, 2020), using the same follow-up period from 2000 to 2011.…”
Section: Discussionmentioning
confidence: 99%